A photo-controlled hyaluronan-based drug delivery nanosystem for cancer therapy. (15th February 2019) - Sun, Feifei; Zhang, Peng; Liu, Yinyin; Lu, Chunbo; Qiu, Yuanhao; Mu, Haibo; Duan, Jinyou
Graphical abstract: Highlights: A hyaluronan-based drug-loaded nanosystem with light responsiveness was prepared. CD44-overexpressed HeLa cells take up the micelles through recognition of HA. Photo-induced product of nanosystem and DOX inhibit proliferation of HeLa together. Abstract: In this paper, a novel photo-controlled drug-loaded nanomicelles were self-assembled by the amphiphile of hyaluronan- o -nitrobenzyl-stearyl chain (HA-NB-SC) with doxorubicin (DOX) encapsulated within the hydrophobic core. DOX-loaded HA-NB-SC nanomicelles are ∼139 nm in diameter. CD44-overexpressed HeLa cells can easily take up HA-NB-SC micelles through recognition of HA moiety. DOX-loaded HA-NB-SC nanomicelles could be disassembled upon UV light (365 nm) and consequently, release DOX at desired pathological sites. Furtherly, nitrosobenzaldehyde derivative, photo-induced products of HA-NB-SC and DOX could inhibit the proliferation of HeLa cells together. This strategy may shed some light on delivery of hydrophobic anti-cancer drugs in a controlled manner.